Functional analysis of TCR gamma delta+ T cells in tumour-infiltrating lymphocytes (TIL) of human pancreatic cancer. - Kitayama, J (1993)
In six patients with advanced pancreatic carcinoma, TIL and tumour-draining lymphocytes (TDL) were isolated from primary pancreatic tumour and regional lymph nodes. In comparison with TDL and peripheral blood lymphocytes (PBL), TIL contained a comparatively higher percentage of TCR gamma delta+ cells, although they were still a small fraction. By 2 weeks culture with rIL-2 and immobilized OKT-3 antibody, the TCR gamma delta+ cells in TIL were preferentially expanded at the early culture periods, although it was temporary. In four cases, the TCR gamma delta+ and CD8+ TCR alpha beta+ TIL were separated by negative sorting using flowcytometry. All the TCR gamma delta+ TIL were CD4-, CD8- (double negative), and one of the TIL lines was mostly composed of delta TCS1+ cells, while the others were delta TCS1-. In comparison with CD8+ TCR alpha beta+ TIL, all the TCR gamma delta+ TIL exhibited much stronger lytic activity against freshly isolated autologous pancreatic cancer cells. However, all the gamma delta+ TIL also exhibited a strong non-MHC-restricted cytotoxicity, and there was no correlation between the lytic pattern and the percentage of delta TCS1+ cells. These data suggest that the TCR gamma delta+ T cells can proliferate vigorously in a certain condition, and if successfully expanded in vitro they might be helpful material for effective adoptive immunotherapy.